Process Philosophy and the Question of Life's Meaning - Brown, Delwin (Religious studies, 1971)
Recent discussions, principally among analytic philosophers, concerning the meaning and the validity of the question of life's meaning' (hereafter referred to as QLM) are significant in several ways. They indicate how analytic philosophy, long charged with sterility, can clarify deeply human questions. They suggest useful avenues of discussion between the analysts and the existentialists, phenomenologists and process philosophers. And they offer some illuminating discriminations between theism and naturalism, and between religious and non-religious understandings of life. But an additional consequence of these discussions is the emergence of a series of challenges to most forms of theism, especially Christianity. In this paper we will be concerned with the latter.